2021
DOI: 10.3389/fimmu.2021.755512
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-Inducible LINC02605 Promotes Antiviral Innate Responses by Strengthening IRF3 Nuclear Translocation

Abstract: Non-coding RNAs represent a class of important regulators in immune response. Previously, LINC02605 was identified as a candidate regulator in innate immune response by lncRNA microarray assays. In this study, we systematically analyzed the functions and the acting mechanisms of LINC02605 in antiviral innate immune response. LINC02605 was up-regulated by RNA virus, DNA virus, and type I IFNs in NF-κB and Jak-stat dependent manner. Overexpression of LINC02605 promotes RNA virus-induced type I interferon product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…However, we observed that miRNAs that were altered at 12 hpi showed similar tendency but subtle changes at 6 hpi, suggesting miRNA responded to SARS-CoV-2 infection as early as 6 hpi ( Figure 2C ). Moreover, several dysregulated miRNA including 4 down-regulated miRNAs (miR-486-5p, miR-451a, miR-206, and miR-142-5p) and 5 up-regulated miRNAs (miR-155-3p, miR-27a-5p, miR-20a-5p, miR-17-5p, and miR-107) were associated with pathophysiology in response to viral replication ( 42 49 ). Among them, miR-486-5p, miR-451a, miR-142-5p, miR-27a-5p, miR-20a-5p, miR-17-5p have been reported to be dysregulated in SARS-CoV-2-infected patients ( 50 53 ), while others such as miR-206, miR-155-3p and miR-107 have not been associated with SARS-CoV-2 viral infection, suggesting that host miRNAs reacting at early stage of SARS-CoV-2 infection might play important roles in host-SARS-CoV-2 interaction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we observed that miRNAs that were altered at 12 hpi showed similar tendency but subtle changes at 6 hpi, suggesting miRNA responded to SARS-CoV-2 infection as early as 6 hpi ( Figure 2C ). Moreover, several dysregulated miRNA including 4 down-regulated miRNAs (miR-486-5p, miR-451a, miR-206, and miR-142-5p) and 5 up-regulated miRNAs (miR-155-3p, miR-27a-5p, miR-20a-5p, miR-17-5p, and miR-107) were associated with pathophysiology in response to viral replication ( 42 49 ). Among them, miR-486-5p, miR-451a, miR-142-5p, miR-27a-5p, miR-20a-5p, miR-17-5p have been reported to be dysregulated in SARS-CoV-2-infected patients ( 50 53 ), while others such as miR-206, miR-155-3p and miR-107 have not been associated with SARS-CoV-2 viral infection, suggesting that host miRNAs reacting at early stage of SARS-CoV-2 infection might play important roles in host-SARS-CoV-2 interaction.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, miR-20a-5p and miR17-5p are found to be up-regulated in influenza A virus-infected patients and extracellular vesicles of lung epithelial tissue, and miR17-5p is proven to promote influenza A virus replication ( 48 , 69 ). Similarly, miR-107 is demonstrated to regulate negatively in response to both DNA and RNA viral infection ( 49 ). Therefore, the specifical alteration of miRNAs implicates that SARS-CoV-2 may manage to repress host antivirus immunity for its pathogenicity.…”
Section: Discussionmentioning
confidence: 99%
“…We identified several noncoding RNAs within the gene modules that otherwise predominantly contained ISGs, including ENSG00000225886 (antisense to IFI6 ); NRIR , a negative regulator of SARS-CoV-2 infection ( 70 ); and LINC02056 , an IFN-inducible transcript with a proposed role in IRF3 nuclear translocation ( 71 ). As is often the case with noncoding genes, functional annotation of others was lacking, such as LINC02051 and LINC02068 ; these are potentially interesting candidates to study in the context of the EC IFN response.…”
Section: Discussionmentioning
confidence: 99%
“…The lncRNA LINC02605 is involved in the antiviral immune response and its knockdown leads to an increased viral replication [ 47 ]. LINC02605 is upregulated in PC-3 cells after the first parabola (P adj to 1 g = 2.9 × 10 −6 ) and even more after parabola 31 (P adj to 1 g = 1.9 × 10 −16 ).…”
Section: Discussionmentioning
confidence: 99%
“…LINC02605 is upregulated in PC-3 cells after the first parabola (P adj to 1 g = 2.9 × 10 −6 ) and even more after parabola 31 (P adj to 1 g = 1.9 × 10 −16 ). It has an effect on hsa-miR-107 regulation on the protein expression of phosphatase and tensin homolog (PTEN) [ 47 , 48 ]. Both miR-107 and PTEN are important players in carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%